Lost. found. - Arnold, Marsha Diane (Roaring Brook Press, 2015)
When a bear loses his bright red scarf in the woods, it is found--and lost again--by a series of animals that use it to keep warm or to have fun, but they disagree over who really owns it and cause a problem that only the scarf's true owner can fix.